Vegetarians and Cardiovascular Risk Factors: Hemostasis, Inflammatory Markers and Plasma Homocysteine - Mezzano, Diego; Muñoz, Ximena; Martínez, Carlos; Cuevas, Ada; Panes, Olga; Aranda, Eduardo; Guasch, Viviana; Strobel, Pablo; Muñoz, Blanca; Rodríguez, Soledad; Pereira, Jaime; Leighton, Federico (Thrombosis and Haemostasis, 1999)
We studied hemostatic and inflammatory cardiovascular risk factors (CVRF), and total plasma homocysteine (tHcy) in 26 vegetarians (23 lacto- or ovolactovegetarians and 3 vegans), matched by age, sex and socioeconomic status with omnivorous controls. Vegetarians had significantly lower proportion of eicosapentaenoic (EPA) and docosahexaenoic (DHA) acids in plasma lipids, significantly shortened bleeding time, and increased blood platelet count and in vitro platelet function (aggregation and secretion). Plasma levels of all coagulation or fibrinolytic factors and natural inhibitors synthesized in the liver were lower in vegetarians than in controls. Whereas for some factors this decrease was statistically significant (fibrinogen, factor VIIc, anti-thrombin III, protein S, plasminogen) for the remaining (factors VIIIc, Vc, prothrombin, protein C) a trend in the same direction was found. For hemostatic proteins of predominantly extrahepatic origin (von Willebrand factor, tPA, PAI-1) this tendency was not present. No significant differences in inflammatory proteins (C-reactive protein and α1-protease inhibitor) were detected in both groups. tHcy was significantly increased in vegetarians, and correlated only with cobalamin levels. The increased platelet function and tHcy found in vegetarians may counteract the known cardiovascular health benefits of vegetarian diet (VD).